PENINGKATAN KETERAMPILAN SOSIAL MELALUI PERMAINAN TRADISIONAL LOMPAT JENGKAL PADA ANAK USIA DINI - Kristina Erlin; M. Sukri; Lukmanulhakim Lukmanulhakim (Universitas Tanjungpura, 2022)
AbstractThis study aims to determine the improvement of social skills through the traditional game of spanking for children aged 5-6 years at the Santa Gemma Sekadau Kindergarten. The reason or the importance of researchers conducting research on improving social skills through traditional jumping spans is to find out how children's social skills increase when the learning method is applied through traditional games of spanning jumps at Santa Gemma Sekadau Kindergarten. The method used is descriptive method with the type of research used is classroom action research. The source of the data for this research was the 8 students of the B4 Kindergarten Santa Gemma Sekadau group. The collaborators in this study were the class B4 teacher, which consisted of 1 person. Data collection techniques used are observation techniques and document studies. The instrument of data collection was through observation sheets, and documentation. The results of the study show (1) Lesson planning is shown when the teacher can prepare lesson plans well. (2) The implementation of learning is shown when the teacher can carry out learning well in accordance with the plans that have been made. (3) The improvement of children's social skills is shown when children want to communicate and socialize, share, cooperate, and participate when playing with their friends.Keywords: Social Skills, Traditional Game of Jump Jengkal